Altered Hippocampo-Cerebello-Cortical Circuit in Schizophrenia by a Spatiotemporal Consistency and Causal Connectivity Analysis - Chen, Xi; Jiang, Yuchao; Chen, Lin; He, Hui; Dong, Li; Hou, Changyue; Duan, Mingjun; Yang, Mi; Yao, Dezhong; Luo, Cheng (Frontiers in Neuroscience, 2017)
A new measure, FOur-dimensional Consistency of local neural Activities (FOCA), was used to investigate the local consistency by integrating the temporal and spatial information of the local region in schizophrenia since previous studies paid insufficient attention to the effects of spatial consistency. In the current study, resting-state fMRI data of 69 schizophrenia patients and 70 healthy controls were collected. FOCA was utilized to investigate the local consistency. Moreover, Granger causal analysis was used to investigate causal functional connectivity among these areas, which exhibited significantly different local consistency between groups. Compared with the healthy controls, the schizophrenia patients exhibited altered local consistency in the prefrontal-thalamic (limbic and basal ganglia)-sensorimotor circuit and altered causal functional connectivity in these areas. These findings suggested that the hippocampus might relate to the positive symptom in schizophrenia and could be considered as an important target for antipsychotic treatment.